The cost of treating diabetic ketoacidosis in the UK: a national survey of hospital resource use. Issue 10 (14th August 2017) - Dhatariya, K. K.; Skedgel, C.; Fordham, R.
Abstract: Aim: Diabetic ketoacidosis is a commonly encountered metabolic emergency. In 2014, a national survey was conducted looking at the management of diabetic ketoacidosis in adult patients across the UK. The survey reported the clinical management of individual patients as well as institutional factors that teams felt were important in helping to deliver that care. However, the costs of treating diabetic ketoacidosis were not reported. Methods: We used a 'bottom up' approach to cost analysis to determine the total expense associated with treating diabetic ketoacidosis in a mixed population sample. The data were derived from the source data from the national UK survey of 283 individual patients collected via questionnaires sent to hospitals across the country. Results: Because the initial survey collection tool was not designed with a health economic model in mind, several assumptions were made when analysing the data. The mean and median time in hospital was 5.6 and 2.7 days respectively. Based on the individual patient data and using the Joint British Diabetes Societies Inpatient Care Group guidelines, the cost analysis shows that for this cohort, the average cost for an episode of diabetic ketoacidosis was £2064 per patient (95% confidence intervals: 1800, 2563). Conclusion: Despite relatively short stays in hospital, costs for managing episodes of diabetic ketoacidosis in adults were relatively high. Assumptions made in the calculations did not consider prolonged hospital stay due to comorbidities or costs incurred as a loss of productivity. Therefore, the actual costs to the healthcare system and society in general are likely to be substantially higher. What's new?: Diabetic ketoacidosis is a commonly encountered metabolic emergency, but the costs of treating the condition remain unknown in the UK. Using individual patient data from the 2014 national survey we conducted a 'bottom‐up' approach to cost analysis. The average cost of an episode of diabetic ketoacidosis in the UK in 2014 was £2064 per patient (95% confidence intervals: 1800, 2563).